(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
to analyze the pregravid and gravid periods in women who gave birth to children with congenital pneumonia, to consider clinical, laboratory and microbiological characteristics, as well as features of the course of this disease in full-term and premature newborns.